Required one Moment, Redundant the Next: John Chrysostom on the Appearance of the Holy Writ - Raphael Yü-sen PENG, (Journal of Research for Christianity in China (JRCC), 2024)
This article examines the views of the 4th century Greek Christian writer John Chrysostom on the appearance of the Holy Writ, and aims to show that John Chrys-ostom neither undervalued nor overvalued the Bible. In his view, the Bible as a product of οἰκονομία is an indispensable means of education in a particular time and space. Its emergence and applicability have been meticulously orchestrated, appearing as both the price of regression and a pathway toward progress. John Chrysostom's emphasis is on spiritual reading leading to the sanctification of the entire person. When humanity, aided by the Holy Writ, transcends all distractions of passion, purifies the soul from impurity, and restores the original relationship between God and humans, as well as interpersonal relationships, the Holy Writ will have fulfilled their historical mission.
Keywords: John Chrysostom, Old Testament, New Testament, creation, καθαρός